The use of a carbonized phenolic formaldehyde resin coated Ni foam as an interlayer to increase the high-temperature strength of C/C composite-Nb brazed joints. Issue 6 (15th March 2022) - Wang, Zeyu; Butt, Hassaan Ahmad; Ma, Qiang; Wang, Zhijie; Li, Manni; Lei, Yucheng
Abstract: A novel carbonized phenolic formaldehyde resin (PF) resin-coated Ni foam was used as an interlayer for brazing carbon fiber reinforced carbon composites (C/C) and Nb using a Ti–Ni filler. At first, uniformly distributed carbonaceous laminae with different mass fractions on the Ni foam surface were acquired after the carbonization process by controlling the concentration of the PF solution. Afterwards, the obtained carbonaceous laminae covered Ni foam composite (C-Nif ) was applied as an interlayer for brazing C/C and Nb via an assembly of C/C/Ti foil/Ni foil/C-Nif interlayer/Ti foil/Nb. The morphologies and microstructures of the carbonization product and the interfacial microstructures of the joints were investigated. The brazing mechanism has been elaborated in detail. With the help of the interconnected porous structure of the Ni foam, the distribution of the in-situ formed (Ti, Nb)2 Ni particles, (Ti, Nb)C ring reinforcements as well as the Nb solid solution were uniformly obtained throughout the brazing seam. As a result, the joint residual stress was effectively released and consequently, the joint shear strength at elevated temperature (1000 °C) reached up to 33 MPa, which is 4.5 times higher than the directly brazed joint without an interlayer.